The Effects of Omega-3 Fatty Acids Supplementation on Gene Expression Involved in the Insulin and Lipid Signaling Pathway in Patients with Polycystic Ovary Syndrome - Nasri, Khadijeh; Hantoushzadeh, Sedigheh; Aghadavod, Esmat; Taghizadeh, Mohsen; Asemi, Zatollah (Hormone and Metabolic Research, 2017)
Limited data are available evaluating the effects of omega-3 fatty acids supplementation on gene expression involved in the insulin and lipid-signaling pathway in women with polycystic ovary syndrome (PCOS). This study was conducted to evaluate the effects of omega-3 fatty acids supplementation on gene expression involved in the insulin and lipid signaling pathway in women with PCOS. This randomized double blind, placebo-controlled trial was done among 60 women aged 18–40 years old and diagnosed with PCOS according to the Rotterdam criteria. Participants were randomly assigned into 2 groups to receive either 1 000 mg omega-3 fatty acids from flaxseed oil containing 400 mg α-linolenic acid (n=30) or placebo (n=30) twice a day for 12 weeks. Gene expressions involved in the insulin and lipid-signaling pathway were quantified in blood samples of PCOS women with RT-PCR method. Quantitative results of RT-PCR demonstrated that compared with the placebo, omega-3 fatty acids supplementation upregulated peroxisome proliferator-activated receptor gamma (PPAR-γ) mRNA (p=0.005) in peripheral blood mononuclear cells of women with PCOS. In addition, compared to the placebo, omega-3 fatty acids supplementation downregulated expressed levels of oxidized low-density lipoprotein receptor (LDLR) mRNA (p=0.002) in peripheral blood mononuclear cells of women with PCOS. We did not observe any significant effect of omega-3 fatty acids supplementation on expressed levels of glucose transporter 1 (GLUT-1) and lipoprotein(a) [Lp(a)] genes in peripheral blood mononuclear cells. Overall, omega-3 fatty acids supplementation for 12 weeks in PCOS women significantly improved gene expression of PPAR-γ and LDLR.
Keywords: supplementation; gene expression; insulin; lipid; polycystic ovary syndrome